Empire of ink : the printers, rogues, and radicals who invented the American newspaper - Wright, Alex, 1966- (Basic Books, 2026)
"No society had ever generated so much ink and paper in so little time. Between the Revolutionary War and the dawn of the twentieth century, the number of American newspapers increased five hundredfold, producing the greatest outpouring of printed matter the world had ever seen. In Empire of Ink, Alex Wright tells the story of how an unruly young democracy found its voice, fueled by a mix of new technologies, bold public policies, and a distinctly American zeal for free expression that unleashed a torrent of newsprint, knitting together a fractious republic. It was a wild, boisterous era populated by gunslinging editors, tramp printers, zealous reformers, brilliant inventors, and literal snake-oil salesmen. Together, they transformed journalism, built a new industry, and helped forge the nation's character. By century's end, this freewheeling press had yielded to corporate interests. Wealthy media barons seized on new technologies and economies of scale to consolidate power, shaping the mass media that would define the twentieth century. Vividly bringing to life a pivotal chapter in American history, Empire of Ink reveals how the same struggles over truth, technology, and power continue to echo into today's digital age"-- Provided by publisher.